2014
DOI: 10.1074/jbc.m114.554998
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Interactions of the Intrinsically Disordered Region between the Helicase and Nuclease Domains of the Archaeal Hef Protein

Abstract: Background: Hef/FANCM participates in interstrand cross-link DNA repair. Results: The predicted intrinsically disordered region (IDR) in Hef was experimentally verified. Proliferating cell nuclear antigen and a RecJ-like protein interact with the IDR individually, but not simultaneously. Conclusion:The IDR in Hef interacts with multiple proteins. Significance: Hef may function in DNA repair by association of its IDR with multiple partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 54 publications
0
44
0
Order By: Relevance
“…In the case of TkoHef, the interaction with PCNA1 does not involve a canonical PIP motif [52], but a disordered region of Hef between the helicase and nuclease domains. Interestingly, these predicted long disordered regions connecting two catalytic domains are a common feature of euryarchaeal Hef and eukaryotic FANCM proteins [50]. So, both creanarchaeal XPF and euryarchaeal Hef proteins can interact with PCNA and display biochemical activities consistent with XPF/Hef being involved in DNA repair and/or replication restart.…”
Section: Biochemical Characterization Of Archaeal Hef/xpfmentioning
confidence: 95%
See 1 more Smart Citation
“…In the case of TkoHef, the interaction with PCNA1 does not involve a canonical PIP motif [52], but a disordered region of Hef between the helicase and nuclease domains. Interestingly, these predicted long disordered regions connecting two catalytic domains are a common feature of euryarchaeal Hef and eukaryotic FANCM proteins [50]. So, both creanarchaeal XPF and euryarchaeal Hef proteins can interact with PCNA and display biochemical activities consistent with XPF/Hef being involved in DNA repair and/or replication restart.…”
Section: Biochemical Characterization Of Archaeal Hef/xpfmentioning
confidence: 95%
“…Consistent with a role of Hef in replication and/or repair, Thermococcus kodakarensis Hef has recently been shown to interact with TkoPCNA1 [50]. In the cell, the replication factor PCNA (Proliferating Cell Nuclear Antigen) encircles double-strand DNA (dsDNA) and enhances e.g.…”
Section: Biochemical Characterization Of Archaeal Hef/xpfmentioning
confidence: 96%
“…Here, we used high-speed atomic force microscopy (HS-AFM) to examine the structure of FliK at the single molecular level and hereby to gain an insight into the hook-length control mechanism. HS-AFM is capable of visualizing protein molecules in action at high spatiotemporal resolution [16,17] and has been proven to be valid not only for ordered proteins [18][19][20][21][22] but also for ID proteins [23][24][25]. Although the NMR data suggested that FliK N would be structurally disordered, HS-AFM observation revealed that a FliK molecule in solution took on a shape of two balls linked by a flexible string and that the N-terminal ball is more stable than the C-terminal ball.…”
Section: Introductionmentioning
confidence: 93%
“…The amino acid sequences of the IDR are generally divergent and sequence alignments do not provide any conserved sequence motif. 21) Three organisms, Thermoplasma volcanium (NP_111072), Picrophilus torridus (AAT42851), and Ferroplasma acidarmanus (YP_008141571), were found in the total genome database as close relatives of T. acidophilum (NP_394502). We made a multiple sequence alignment of the Gins51 homologs from these data and found that the interdomain regions are indeed highly divergent, in contrast to the two distinct domains.…”
Section: Assignment Of the Linker Region Between A-and B-domainsmentioning
confidence: 99%